EVALUASI ACTION DAN RESULT CONTROL UNTUK MENINGKATKAN KINERJA BAGIAN PRODUKSI CV X DI KEDIRI - Rifky Marvindo Soendoro (Perpustakaan Universitas Surabaya, 2015)
In today's era of globalization, the competition in the business world becomes more intense. A company generally always required in order to provide good performance and quality. One thing to note the company for achieving maximum performance quality of the provision is the management system that controls the application of controlled and well implemented. The success in the implementation of the control system will affect the management and increase the motivation of human resources in the company so that it can directly affect the performance provided by the company. The purpose of this study is the author tries to analyze the topic of the application of control and result control action to improve employee motivation production department at CV. X so that the performance given by the human resources CV. X will increase. This study used a qualitative approach using interviews, observation, and literature. The findings in this study indicate that management control systems by CV. X is less well targeted in influencing employee motivation. This has an impact on the results achieved by each employee. Therefore, this study attempts to provide recommendations for improvement in the implementation of management control systems, especially in the action and result control on CV. X, so that the company can obtain maximum results and achieve the performance objectives of the CV. X.